Trends in incidence and prevalence of osteoarthritis in the United Kingdom: findings from the Clinical Practice Research Datalink (CPRD). Issue 6 (June 2020) - Swain, S.; Sarmanova, A.; Mallen, C.; Kuo, C.F.; Coupland, C.; Doherty, M.; Zhang, W.
Summary: Objective: This study aimed to explore the incidence and prevalence of OA in the UK in 2017 and their trends from 1997 to 2017 using a large nationally representative primary care database. Design: The UK Clinical Practice Research Datalink (CPRD) comprising data on nearly 17.5 million patients was used for the study. The incidence and prevalence of general practitioner diagnosed OA over a 20 years period (1997–2017) were estimated and age-sex and length of data contribution standardized using the 2017 CPRD population structure. Cohort effects were examined through Age-period-cohort analysis. Results: During 1997–2017, there were 494, 716 incident OA cases aged ≥20 years. The standardised incidence of any OA in 2017 was 6.8 per 1000 person-years (95% CI 6.7 to 6.9) and prevalence was 10.7% (95% CI 10.7–10.8%). Both incidence and prevalence were higher in women than men. The incidence of any-OA decreased gradually in the past 20 years at an annual rate of −1.6% (95%CI -2.0 to −1.1%), and the reduction speeded up for people born after 1960. The prevalence of any-OA increased gradually at an annual rate of 1.4% (95% CI 1.3–1.6%). Although the prevalence was highest in Scotland and Northern Ireland, incidence was highest in the East Midlands. Both incidence and prevalence reported highest in the knee followed by hip, wrist/hand and ankle/foot. Conclusion: In the UK approximately one in 10 adults have symptomatic clinically diagnosed OA, the knee being the commonest. While prevalence has increased and become static after 2008, incidence is slowly declining. Further research is required to understand these changes.